2014
DOI: 10.1590/1982-0216201425212
|View full text |Cite
|
Sign up to set email alerts
|

Estado mental e impacto do zumbido em idosos

Abstract: Objetivo analisar o desempenho de uma população idosa no Mini Exame do Estado Mental; verificar os resultados da aplicação do Tinnitus Handicap Inventory (THI); averiguar a interferência das variáveis gênero, escolaridade e zumbido no desempenho geral no MEEM e THI; verificar possíveis relações do estado mental com o autorrelato das características psicoacústicas e escala emocional do THI. Métodos estudo clínico descritivo, exploratório, quantitativo e qualitativo em que se submeteram ao MEEM e THI, 108 vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
0
0
2
Order By: Relevance
“…A research highlighted that the practice of physical activities is a determining factor for a lesser negative impact of the tinnitus among the elderly, possibly because it promotes the wellbeing and diminishes the discomfort sensation. 20 In the analysis of THI classification, a higher number of individuals with impact considered negligible and mild corroborates other national studies, 22 but differs from others 2,23,24 that observed a greater number of individuals with negligible, mild and moderate discomfort. As in our study sample was composed of adult and elderly individuals, it is believed that this data can be taken into consideration, once the elderly can be more resilient, being able to adapt faster to unfavorable situations.…”
Section: Discussionsupporting
confidence: 82%
“…A research highlighted that the practice of physical activities is a determining factor for a lesser negative impact of the tinnitus among the elderly, possibly because it promotes the wellbeing and diminishes the discomfort sensation. 20 In the analysis of THI classification, a higher number of individuals with impact considered negligible and mild corroborates other national studies, 22 but differs from others 2,23,24 that observed a greater number of individuals with negligible, mild and moderate discomfort. As in our study sample was composed of adult and elderly individuals, it is believed that this data can be taken into consideration, once the elderly can be more resilient, being able to adapt faster to unfavorable situations.…”
Section: Discussionsupporting
confidence: 82%
“…Dentre estes, Transtornos Mentais Comuns (TMC) que se caracterizam por um conjunto de sintomas incluindo ansiedade, insônia, fadiga, irritabilidade, esquecimento, dificuldade de concentração e queixas somáticas 3 , apresentam-se como uma das morbidades psíquicas mais prevalentes, atingindo aproximadamente um terço da população em indivíduos de diferentes faixas etárias 4,5 . Embora não sejam tão graves como distúr-bios psicóticos, TMC podem representar um importante problema de saúde pública devido à sua alta prevalência e graves efeitos sobre o bem -estar pessoal, familiar, trabalho e uso de serviços de saúde 6 .…”
Section: Introductionunclassified
“…Esse cenário concorre para a necessidade de atenção em saúde específica e diferenciada a esses indivíduos que são mais acometidos por doenças crônicas, declínio sensorial, limitações físicas, isolamento social e os problemas de saúde mental¹ , ². Entre os problemas de saúde mental, os transtornos mentais comuns (TMC), caracterizados por sintomas como ansiedade, transtornos somatoformes, insônia, fadiga, irritabilidade, esquecimento, dificuldade de concentração e queixas somáticas³, estão entre os mais prevalentes, atingindo cerca de um terço da população mundial em diferentes faixas etárias 4,5 . Em idosos, os estudos mostram que a prevalência de TMC varia entre 29,7% entre idosos residentes no município de Campinas -SP² e 47,7% em idosos residentes em Jequié-BA 6 .…”
Section: Introductionunclassified